Value Added Tax Fraud in the Judgments of the Court: Why We Should Know Our Business Partners? - Burianova, Olga (European Journal of Applied Sciences, 2024)
This article analyses the judgment of the Supreme Administrative Court, which concerns carousel fraud in Value Added Tax. In particular, it examines the issue of supplier-customer relationships in defined types of markets where carousel fraud can be traced. The aim of the paper is to analyse the judgment of the Supreme Administrative Court and to point out the threat of wrongly selecting a supplier and the threat to added value in economic activity. The resulting question is: Why should we know our business partners? The results of this paper can be a lesson for entrepreneurs, but also for other entities trying to minimize the impact of these frauds on the business of the parties involved and the economy as a whole.